Experimental Assessments of Treating Effect on Retaining Walls for Loess Slopes under Long-Term Rainfall - Guodong Liu; Zhijun Zhou; Shiqiang Xu; Wenjing Mi (Advances in Civil Engineering)
Failures of treated slope occurring in China are at a continually increasing rate, and the huge number of treated loess slopes is calling for a postevaluation; however, no mature technique is in place. Based on an actual loess slope in Shaanxi Province treated by retaining wall, indoor geotechnical and model tests were conducted, revealing the rainwater infiltration process and pressure variations behind the wall, and the processes were then adopted to perform the postevaluation of the treated slope. The results proposed that effectual measures hence needed to be taken so as to avert rainwater infiltrating along the wall face and back or flowing through the wall body, which can soften the soil of the slope bottom. Although the wet front was developed by the rainfall process, it cannot be used as the boundary between saturated and unsaturated areas. Despite the peculiarly large soil pressure upon the wall back at the top layer, the soil pressure increases to a large value and then decreases with the depth. The model test results and investigation results were used to conduct the postevaluation of the prototype slope, which formed a postevaluation frame relevant to other slope postevaluations.